NMR analysis of phosphoric acid distribution in porous fuel cell catalysts - Zhang, En; Fulik, Natalia; Zhang, Hanyue; Bevilacqua, Nico; Zeis, Roswitha; Xu, Fei; Brunner, Eike; Kaskel, Stefan (Chemical Communications, 2021)
Understanding the interaction of phosphoric acid and porous electrocatalysts is of vital importance for a rational design of high performance phosphoric acid based fuel cells on a molecular level. We demonstrate for the first time that NMR spectroscopy can be used for elucidating the preferred distribution sites of phosphoric acid in various nanoporous carbons. A pore size dependent negative chemical shift of31P is observed, serving as a distinct signature of pore occupation, and applied for analysing a commercial catalyst (Pt@Vulcan) as a practical application.
CRIS-Team Scopus Importer:2022-04-14